Early palliative psychological therapy based on the CALM model to improve quality of life and emotional health in patients with breast cancer. Analysis of quality of care: A mixed-methods study in Mexico - Domínguez-Morán, Abel; Pavón-León, Patricia; Meda-Lara, Rosa Martha (Psicooncología, 2025)
Objective: To evaluate the impact of an early palliative psychological intervention, based on the CALM model, on quality of life and emotional symptoms in recently diagnosed Mexican breast cancer patients, as well as to explore their perceptions regarding the quality of care received. Methods: A sequential explanatory mixed-methods study was conducted using a quasi-experimental pretest-posttest design. The sample comprised 10 women (5 in the experimental group and 5 in the control group) treated at a secondary-level hospital. Validated instruments were employed to assess quality of life (FACT-B), depression (BDI-II), and anxiety (BAI), in addition to baseline qualitative interviews. The experimental group received four individual psychotherapy sessions based on the CALM model over a three-month period. Quantitative data were analyzed using Mann-Whitney U, Wilcoxon signed-rank tests, and Cohen’s d effect size. Qualitative data were examined through inductive thematic analysis. Results: The experimental group demonstrated improvements across all quality of life domains, with statistically significant changes observed in emotional well-being. In contrast, the control group exhibited an overall decline, with a significant reduction in functional well-being. Anxiety levels increased in the control group, whereas they decreased to minimal levels in the experimental group. Depressive symptoms remained stable in the experimental group but increased in the control group. Effect sizes were large in several domains. Qualitative findings revealed perceived deficiencies in the quality of care, particularly regarding emotional support. Conclusions: The early palliative psychological intervention based on the CALM model yielded positive effects on emotional health and perceived quality of life among participants.
Keywords: Breast cancer; Mental Health; Palliative care; Psychosocial intervention; Psycho-onchology; Quality of life